2000
DOI: 10.1127/archiv-hydrobiol/150/2000/169
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of free amino acids as an early indication for physiological stress (nitrogen overload) due to elevated ammonium levels in vital Stratiotes aloides L. stands

Abstract: The relationship between the nitrogen and the free amino acid content in Stratiotes aloides L. was investigated for 11 healthy stands in the Netherlands. In the shoots, the mean free asparagine and free arginine levels were strongly correlated with the mean total N concentrations and the ammonium concentrations in the water layer. The percentage of total N present as free amino acids varied from 5.4 % to 27.5 % between the stands. In the stands with the highest total N levels, up to 92 % of the nitrogen in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…However, the high-NH 4 ? concentration in water column caused more severe physiological stress than sediment, possibly due to the very low-R/S ratio of submersed plants in eutrophic environment (Smolders et al, 2000), which is consistent with our result. Thus, these results together indicate that the effects of eutrophic environment on submersed macrophytes dependent on sediment types, water NH 4…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, the high-NH 4 ? concentration in water column caused more severe physiological stress than sediment, possibly due to the very low-R/S ratio of submersed plants in eutrophic environment (Smolders et al, 2000), which is consistent with our result. Thus, these results together indicate that the effects of eutrophic environment on submersed macrophytes dependent on sediment types, water NH 4…”
Section: Discussionsupporting
confidence: 82%
“…However, Zhu et al (2012a) found that significant effects of sediment fertility on mechanical properties of the stems of Hydrilla verticillata (L.f.) Royle, with the higher mechanical resistance in the mesotrophic sediment than the fertile and infertile sediments. These conflicting results may be due to biochemical and anatomical differences among the various plant species (Smolders et al, 2000;Cao et al, 2007;Xiong et al, 2010), as biomechanical properties of plants are largely determined by the plant chemical composition, e.g. cellulose and lignin contents, and anatomic structure (Undersander et al, 1977;Usherwood et al, 1997;Lamberti-Raverot & Puijalon, 2012;Zhu et al 2012a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important factor is light limitation, which may arise from increase in epiphyton, phytoplankton, and sedimentation (Philip et al, 1978;Smolders et al, 1996a;Arts, 2002). Physiological stress resulting from high NH 4 + concentrations in water column may also contribute to the decline of macrophytes (Smolders et al, 1996b(Smolders et al, , 2000Nimptsch and Pflugmacher, 2007). High water column NH 4 + concentrations reduce growth of Ceratophyllum demersum and disturb carbon and nitrogen metabolism in Potamogeton crispus and Stratios aloides (Best, 1980;Smolders et al, 1996bSmolders et al, , 2000Cao et al, 2004;Tylová et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, the observed disproportional accumulation of glutamine can be considered an indication of physiological stress due to the elevated NH 4 + levels in the water layer (Näsholm et al 1994;Huhn and Schulz 1996;Smolders et al 2000). Such a chronic exposure to NH 4 + (i.e., several months or years) will most likely lead to the classically reported visual symptoms like chlorosis of leaves and the suppression of growth (Britto and Kronzucker 2002).…”
Section: Ecological Implicationsmentioning
confidence: 99%